Associations of human papillomavirus genotypes and cervical vascular abnormality in a cohort of women underwent colposcopy, a retrospective study of 6716 patients - Zhang, Yulong; Li, Haibo; Li, Xiaowen; Li, Zhelong; You, Qianru; Yi, Huan; Su, Yanzhao; Zheng, Xiangqin; Chen, Yusha; Chen, Jiancui (Frontiers in Oncology, 2023)
Abstract: Aims: Abnormal vessel patterns are specific signs in patients with early cervical abnormality and cervical carcinoma by colposcopy, but the impact of human papillomavirus (HPV) infections on abnormal vessel patterns remains unknown. Methods: A total of 6716 female patients with HPV infections or cytological abnormalities who underwent a colposcopy following abnormal cervical cancer screening results were included in the study. The final pathological diagnosis was confirmed to be the most severe pathological grade across cervical biopsy, endocervical canal curettage (ECC) and conization. Univariate and multivariate logistic regression analyses were used to investigate the association between HPV infections and abnormal vessel patterns, adjusting for age, gravidity and parity. Results: There were 6124 normal vascular cases by colposcopy and 592 cases with cervical vascular abnormality. The prevalence of HPV infections was 4284 (70%) in normal patients, and the prevalence of HPV infections was 479 (80%) in cervical vascular abnormality patients. HPV high-risk type 16 infection alone increased the risk of cervical heteromorphic blood vessels (aOR=3.619, 95% CI: 2.52 5.198). HPV 16 and 33 alone (other than the commonly recognized subtype of 18) or coinfection of these two genotypes could increase the risk of cervical punctate vascular and cervical vascular mosaic features and abnormal cervical blood vessels. An increased risk of abnormal cervical lesions was observed for HPV 16 and 33 alone or combined in coinfection compared to the negative group. The risk of cervical vascular abnormality was increased 11-fold by coinfection with HPV 16 and 33 (aOR=11.18, 95% CI: 4.74 26.38, P<0.001). HPV 16, 33 alone or combined in coinfection were associated with an increased risk of lesions more advanced than high-grade squamous intraepithelial lesion (HSIL) when compared to the negative group. The risk of lesions more advanced than HSIL was up to 28-fold higher in the coinfection with HPV 16 and 33 group than in the negative group (aOR=28.32, CI: 12.09 66.33, P<0.001). Conclusion: HPV16 and 33 are the most dangerous HPV genotypes correlated with abnormal vascular patterns. Combined HPV16 and HPV33 infection increases the risk of abnormal vascular patterns. Combined HPV16 and HPV33 infection increases the risk of developing HSIL+.